South African refugee law and policy in relation to the international refugee regime - De la Hunt, Virginia Lee Anne (Department of Public Law, 2026)
It has been said that the twenty-first century will be characterised by two phenomena: the explosion of the world's population (at present at about five billion) and an almost exponential increase in migration. 1 In the past, host countries generally regarded migratory movements as a source of development. In recent years, however, they have come to be perceived as a threat to the well-being and security of the host country and those people living there who have the right of citizenship. 2 Almost every book or article on the subject of refugee law begins with statistics indicating the growing number of refugees (usually with a note that most refugees are from African countries), a comment about the causes of refugee movement, followed by the assertion that there is little evidence that numbers of refugees will decline significantly in the foreseeable future. Nations, particularly those in the developed world, 3 are involved in an attempt to reconcile national self-interest with the commitment to sheltering "the huddled masses"4 of forced migrants. The result has been a swing away from a preoccupation with obligations assumed by treaty or convention, or extant in international customary law, to the introduction by countries in the developed world of increasingly restrictive policies with regard to the acceptance of refugees. 5